Circadian modulation of long-term sensitization in Aplysia - Fernandez, Raymond I. (National Academy of Sciences, 2003)
As the mechanisms for learning and memory are elucidated, modulation of learning and memory becomes a central issue. We studied the modulation of learning and memory by investigating the circadian regulation of short- and long-term sensitization of the siphon withdrawal reflex in Aplysia. We found that Aplysia exhibited diurnal and circadian rhythms of long-term sensitization (LTS) with significantly greater LTS occurring when animals were trained and tested during the day relative to those trained and tested at night. In contrast to the modulation of LTS, short-term sensitization was not regulated by the circadian clock. Time of training rather than time of testing determined the circadian rhythm of LTS. Animals trained during the subjective day demonstrated LTS when tested during either the day or the night. Conversely, when animals were trained during the night, LTS was not observed when animals were tested either at night or during the day. Thus, the circadian rhythm of LTS is a rhythm in learning rather than a rhythm in recall. The threshold required to elicit siphon withdrawal and the duration of siphon withdrawal were not regulated by the circadian clock. These results indicate that the circadian oscillator exerts strong modulatory influences on one form of long-term memory in Aplysia.